What Are the Long Nostrils of YHWH? - Amzalag, Nisim (Religions, 2017)
The mention of YHWH's nostrils (ʾapayīm) in the Bible is classically interpreted as a metonymy of the face and/or a metaphor for anger. The reference to their length and even to their elongation, however, rules out any entirely satisfying explanation in this semantic context. If this term is construed as a tuyère, as is identified in Dan 10:20, the use of ʾapayīm in Ex 15:8 becomes clear. This interpretation also explains the denotation of patience and loving-kindness as ʾerek ʾapayīm (the so-called long nostrils of YHWH) because the air pressure generated by a blast from a tuyère (=its power) decreases proportionally to its length. Accordingly, the liturgical formulae that includes this expression (Ex 34:6; Num 14:18; Joel 2:13; Jon 4:2; Pss 86:15; 103:8; 145:8; Neh 9:17) praise YHWH for the forbearance of voluntarily restraining the power of his reaction to annoying events on earth. This interpretation also clarifies the use of ʾap/ʾapayīm in Isa 48:9; Jer 15:15, and Nah 1:3. Furthermore, these last-mentioned instances reveal that beyond their metaphoric meaning, the divine ʾapayīm evoke an essential attribute of YHWH. The significance of these findings is discussed in view of the duality of anthropomorphic and aniconic representations of YHWH in ancient Israel.